Genome-Wide Identification and Characterization of the PERK Gene Family in Gossypium hirsutum Reveals Gene Duplication and Functional Divergence - Qanmber, Ghulam (Int J Mol Sci, 2019)
Proline-rich extensin-like receptor kinases (PERKs) are an important class of receptor kinases in plants. Receptor kinases comprise large gene families in many plant species, including the 15 PERK genes in Arabidopsis. At present, there is no comprehensive published study of PERK genes in G. hirsutum. Our study identified 33 PERK genes in G. hirsutum. Phylogenetic analysis of conserved PERK protein sequences from 15 plant species grouped them into four well defined clades. The GhPERK gene family is an evolutionarily advanced gene family that lost its introns over time. Several cis-elements were identified in the promoter regions of the GhPERK genes that are important in regulating growth, development, light responses and the response to several stresses. In addition, we found evidence for gene loss or addition through segmental or whole genome duplication in cotton. Gene duplication and synteny analysis identified 149 orthologous/paralogous gene pairs. Ka/Ks values show that most GhPERK genes experienced strong purifying selection during the rapid evolution of the gene family. GhPERK genes showed high expression levels in leaves and during ovule development. Furthermore, the expression of GhPERK genes can be regulated by abiotic stresses and phytohormone treatments. Additionally, PERK genes could be involved in several molecular, biological and physiological processes that might be the result of functional divergence.